1995
DOI: 10.1038/374566a0
|View full text |Cite
|
Sign up to set email alerts
|

RPA involvement in the damage-recognition and incision steps of nucleotide excision repair

Abstract: Human replication protein (RPA) functions in DNA replication, homologous recombination and nucleotide excision repair. This multisubunit single-stranded DNA-binding protein may be required to make unique protein-protein contacts because heterologous single-stranded binding proteins cannot substitute for RPA in these diverse DNA transactions. We report here that, by using affinity chromatography and immunoprecipitation, we found that human RPA bound specifically and directly to two excision repair proteins, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
327
1
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 389 publications
(346 citation statements)
references
References 29 publications
15
327
1
2
Order By: Relevance
“…RPA is a highly conserved, single-stranded DNA-binding multisubunit protein complex involved in eukaryotic DNA replication, recombination and repair. 3,5 Previous experimental studies in colon cancer cell lines have reported a reduction in DNA replication activity in parallel with the reduction of RPA1 protein suggesting a crucial role of RPA complex for the proliferative activity of colon cancer cells. 14 However, there is no previous study investigating the in vivo expression of RPA proteins in human colon cancer tissues.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…RPA is a highly conserved, single-stranded DNA-binding multisubunit protein complex involved in eukaryotic DNA replication, recombination and repair. 3,5 Previous experimental studies in colon cancer cell lines have reported a reduction in DNA replication activity in parallel with the reduction of RPA1 protein suggesting a crucial role of RPA complex for the proliferative activity of colon cancer cells. 14 However, there is no previous study investigating the in vivo expression of RPA proteins in human colon cancer tissues.…”
Section: Discussionmentioning
confidence: 97%
“…3,4 Moreover, RPA is involved in DNA recombination and repair. [5][6][7][8] Additionally, it has also been implicated in the regulation of apoptosis and gene expression. 9 Links between RPA and transcription have been postulated based on the observed interactions between RPA and Gal4, VP16, p53, Stat3, RBT1 and menin.…”
mentioning
confidence: 99%
“…The binding of p53 with CSB is consistent with a role of p53 in damage recognition because CSB, together with CSA, are thought to ®rst recognize the stalled transcription complex (Hanawalt, 1994;Selby and Sancar, 1994;Drapkin et al, 1994b). Repair of damaged DNA could also be enhanced by the association of p53 with RPA, which, in complex with the XPA gene product (He et al, 1995), is believed to be recruited next to the site of the lesion (Hanawalt, 1994;Selby and Sancar, 1994;Drapkin et al, 1994). The TFIIH repairosome is thought to be targeted to the DNA at this point, probably through its association with XPA (Park et al, 1995).…”
Section: Discussionmentioning
confidence: 52%
“…RPA is involved in the early stage of NER by interacting with XPA on damaged DNA, which allows the stable RPA-XPA complex to form on damaged DNA [22][23][24][25]27]. Since the zincfinger mutant failed to support NER, we were interested in examining whether the mutation at the zinc-finger domain affects XPA-DNA interaction.…”
Section: Zinc-finger Domain Of Rpa Is Not Necessary For Its Stimulatomentioning
confidence: 99%
“…In nucleotide excision repair (NER), RPA forms a complex with Xeroderma pigmentosum group A complementing protein (XPA) [22][23][24][25], a protein that specifically recognizes UV damage [26]. RPA stimulates the interaction of XPA with DNA through an RPA-XPA complex at damaged DNA sites [23,24,27].…”
Section: Introductionmentioning
confidence: 99%